Fortune Playhouse, Golden Lane - Wise, William; Shepherd, G. (Tufts Archival Research Center, 2008)
Western exterior view with a plan of the site and vicinity. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 2.